Should bank capital regulation be risk sensitive? - Toni Ahnert; James Chapman; Carolyn Wilkins (Bank of Canada, 2018)
We present a simple model to study the risk sensitivity of capital regulation. A banker funds investment with uninsured deposits and costly capital, where capital resolves a moral hazard problem in the banker's choice of risk. Investors are uninformed about investment quality, but a regulator receives a signal about it and imposes minimum capital requirements. With a perfect signal, capital requirements are risk sensitive and achieve the first-best levels of risk and intermediation: safer banks attract cheaper deposit funding and require less capital. With a noisy signal, risk-sensitive capital regulation can implement a separating equilibrium in which low-quality banks do not participate. We show that the degree of risk sensitivity is non-monotone in the precision of the signal and in investment characteristics. Without a signal, a leverage ratio still induces the efficient risk choice but leads to excessive or insufficient intermediation.
Keywords: G21; G28; 330; Financial institutions; Financial system regulation and policies